2002
DOI: 10.1076/ceyr.24.4.296.8415
|View full text |Cite
|
Sign up to set email alerts
|

Lens membrane fraction associated intermediate filaments of different aged rats

Abstract: The NSMF may represent a domain of the lens plasma membrane particularly important in interaction between plasma membrane and cytoskeleton and as the membrane-cytoskeleton protein architecture of rat lens changes over the first 20 days of life, the changes are readily detected in the different membrane fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 26 Immunohistochemical studies indicate vimentin, a major type III IF protein, is expressed in the lens epithelium and fiber cells, although the expression pattern changes based on lens age and region. 4 , 27 , 28 Our results indicate vimentin is most abundant in the very outer fiber cells of the DF region and its abundance decreases in the RZ and further into the lens. Because we analyzed the plasma membrane fraction, this decrease in vimentin signal at the RZ could be due to either reduced vimentin expression, increased solubility of the protein, or decreased association with the plasma membrane.…”
Section: Discussionmentioning
confidence: 63%
“… 26 Immunohistochemical studies indicate vimentin, a major type III IF protein, is expressed in the lens epithelium and fiber cells, although the expression pattern changes based on lens age and region. 4 , 27 , 28 Our results indicate vimentin is most abundant in the very outer fiber cells of the DF region and its abundance decreases in the RZ and further into the lens. Because we analyzed the plasma membrane fraction, this decrease in vimentin signal at the RZ could be due to either reduced vimentin expression, increased solubility of the protein, or decreased association with the plasma membrane.…”
Section: Discussionmentioning
confidence: 63%
“…Crystallins account for approximately 90% of the extrinsic protein, with the remainder comprising cytoskeletal and other proteins (Cenedella and Fleschner 1992). A comparison of the cytoskeletal components vimentin, phakinin, and filensin in the NSMF and 25/45 fractions showed that these proteins differed quantitatively but not qualitatively between the two membrane fractions in both bovine and rat lenses (Fleschner 1998, 2002). …”
Section: Introductionmentioning
confidence: 98%